1994
DOI: 10.3354/meps112067
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory by reef fishes and the production of dimethyl sulfide and acrylic acid

Abstract: The content of dimethylsulfoniopropionate (DMSP) in selected marine reef macrophytes was examined and related to levels of DMSP and one of its decomposition products, dimethylsulfide (DMS), in guts of herbivorous fish. Concentrations of short-chain fatty acids and acrylic acid (ACR), another decomposition product of DMSP, were also measured in gut contents. The fatty acid data provide evidence for bacterial fermentation within fish intestines. Unlike previous observations of gut microflora, the concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
3
38
1
Order By: Relevance
“…Prior studies of muscle DMSP in wild-caught fish of a number of species (not including menhaden) have found that concentrations are usually < 20 nmol g -1 , and concentrations of ≥100 nmol g -1 are commercially problematic, because the DMS liberated during some types of processing can impart unsatisfactory tastes and odors (Motohiro 1962, Iida et al 1986, Dacey et al 1994. Our data show that in menhaden a single feeding of Prorocentrum micans drives concentrations in the swimming muscles and carcass (free of the gastrointestinal tract) to far higher levels (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies of muscle DMSP in wild-caught fish of a number of species (not including menhaden) have found that concentrations are usually < 20 nmol g -1 , and concentrations of ≥100 nmol g -1 are commercially problematic, because the DMS liberated during some types of processing can impart unsatisfactory tastes and odors (Motohiro 1962, Iida et al 1986, Dacey et al 1994. Our data show that in menhaden a single feeding of Prorocentrum micans drives concentrations in the swimming muscles and carcass (free of the gastrointestinal tract) to far higher levels (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Prior information on DMSP in fish feces is sketchy (Ackman et al 1966, Dacey et al 1994. There is, however, a growing literature on DMSP in copepod and euphausid feces, emphasizing that the incorporation of DMSP into feces can greatly affect its dynamic fate by tending to send the DMSP to the bottom, facilitate its release to the water column, or enhance its accessibility to microbial metabolism (Daly & DiTullio 1996, Kwint et al 1996, Tang 2001, Yoch 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Algae appear to synthesize DMSP as follows: methionine 3 4-methylthio-2-oxobutyrate 3 4-methylthio-2-hydroxybutyrate 3 4-dimethylsulfonio-2-hydroxybutyrate 3 DMSP (42). Only a limited number of species of algae and halophytes are capable of DMSP biosynthesis (28,29,54,55), and its concentration can vary considerably from one species to another (55).…”
Section: Sources Of Dmspmentioning
confidence: 99%
“…Only a few species of higher plants have a high DMSP content, either strictly terrestrial plants such as sugar cane (Saccharum) and Wollastonia biflora and intertidal plants such as some species of Spartina (Otte et al, 2004;Dacey et al, 1987). The only study so far that has investigated the occurrence of DMSP in seagrasses was carried out by Dacey et al (1994) who attributed the occurrence of DMSP in samples from three species (Halodule wrightii, Syringodium filiforme, Thalas- * Corresponding author. Fax: +32 4 3669729.…”
Section: Introductionmentioning
confidence: 99%